Sociological analysis of children’s attitudes at the age of 11-15 years old physical education and healthy lifestyle - Denisov R.O.; Ponomarev V.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study is to conduct a sociological analysis of the attitude of children aged 11-15 years to physical education, on the basis of which to draw certain conclusions and give suggestions to specialists. Methods and structure of the study. 53 schoolchildren of Krasnoyarsk aged 11-15 years took part in the sociological survey. A questionnaire was developed that included 15 questions that respondents had to answer, on the basis of which the sociological picture of adolescents’ attitudes to physical education was determined.